2011
DOI: 10.1007/s00436-011-2743-3
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis hominis as a contributing risk factor for development of iron deficiency anemia in pregnant women

Abstract: Intestinal parasitic infection increases the risk of developing iron deficiency anemia (IDA) during pregnancy. The objective of this study was to assess Blastocystis hominis as a contributing risk factor for development of IDA in pregnant women. A total of 200 fecal specimens from 120 pregnant women with IDA (mean Hb = 9.6 g/dl), and 80 non-anemic controls were examined for Blastocystis. Fecal specimens were examined by the formalin/ethyl-acetate concentration technique, iron hematoxylin staining, modified Zie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…infection has been identified as a contributing factor to the pathogenesis of iron deficiency anemia in pregnant women. 40 In this study, we found a correlation between ST1 subtype infection and anemia (P = 0.008); however, the predominant ST3 subtype, ST2 or ST4 all had no associations with anemia. This is different from previous findings in pregnant women reporting no correlation between Blastocystis subtypes and anemia.…”
Section: Discussioncontrasting
confidence: 49%
“…infection has been identified as a contributing factor to the pathogenesis of iron deficiency anemia in pregnant women. 40 In this study, we found a correlation between ST1 subtype infection and anemia (P = 0.008); however, the predominant ST3 subtype, ST2 or ST4 all had no associations with anemia. This is different from previous findings in pregnant women reporting no correlation between Blastocystis subtypes and anemia.…”
Section: Discussioncontrasting
confidence: 49%
“…Colombian studies in school children identified this parasite as common, with over 50% prevalence [ 21 , 39 ]. Despite its debated pathogenicity, Blastocystis hominis has been reported to cause or be associated with abdominal pain and diarrhea [ 76 ], hematological abnormalities [ 77 ], pregnancy-related anemia [ 78 ], and immunosuppression [ 79 ]. Additionally, Ramirez et al [ 80 ] reported that 72% of children positive for Blastocystis hominis were asymptomatic, with just 11% showing abdominal pain and 2% diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…among humans in contact with animals was 35.7%, which was in accordance with previous reports of human blastocystosis in Egypt, regardless of the state of contact with animals. A prevalence of 22.4% was reported among subjects from Dakahlia governorate [38] , while it was 33.3% among patients complaining of GIT symptoms [39] and 26.5% among pregnant women [40] . The situation was quite similar in other developing countries: a prevalence of 41% was reported among animal handlers from Malaysia [27] , 26.1% in subjects from rural communities in Nepal [41] and 37.2% in Thailand [42] .…”
Section: Discussionmentioning
confidence: 99%